Kinetic Study of Saponin Extraction from Sapindus rarak DC by Ultrasound-Assisted Extraction Methods - Aininu Nafiunisa; Nita Aryanti; Dyah Hesti Wardhani (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
Saponin is an important plant-derived compound that is commonly found in sapindaceae plants, such as Sapindus rarak DC. Saponin is extensively used in plenty of industries as a detergent or emulsifying agent in cleansers, shampoos, and cosmetics. The extraction of saponin was previously studied and shows that the extraction assisted by ultrasonic waves was found to be an effective method. However, the previous studies have rarely examined the extraction kinetic study of the ultrasound-assisted extraction (UAE). In the present study, the extraction of saponin from Sapindus rarak DC and its extraction kinetics is conducted. The results show that the highest saponin yield of 354.92 (mg of saponin per gram of dry feed) was obtained from the extraction using a solid-to-liquid (S/L) ratio of 1:50 (w/v) at 50 °C. The amount of extracted saponin increased with the increase of extraction temperature as well as the solute ratio in the solution. However, increasing the temperature to 60 °C decreased the saponin yield. The results of a simple kinetics study of saponin extraction also show that the second-order kinetics model can better describe the UAE process, with an R2 value of 0.929 and a rate coefficient of 0.00495 L.g-1.min-1. The experimental results agree well with the practical calculations obtained using the second-order kinetics model based on an average error of 6.79%.